Elabela Attenuates the TGF-β1-Induced Epithelial-Mesenchymal Transition of Peritoneal Mesothelial Cells in Patients Receiving Peritoneal Dialysis - Xie, Shunyun; Xu, Feng; Lu, Yue; Zhang, Yixian; Li, Xinyang; Yu, Mengyuan; Cui, Wenpeng (Frontiers in Pharmacology, 2022)
Peritoneal fibrosis (PF), a common complication in patients receiving peritoneal dialysis (PD), is primarily caused by the epithelial-mesenchymal transition (EMT) of human peritoneal mesothelial cells (HPMCs). PF is the main reason for patients on PD to withdraw from PD. Effective treatment is unavailable for this complication at present. Elabela (ELA) is a polypeptide hormone secreted by the vascular endothelium and kidney. Peptide hormones ELA and apelin (APLN) have various protective effects on the cardiovascular and urinary systems and have potential therapeutic effects on organ fibrosis. ELA and APLN are less studied in PD population. Here, we aimed to investigate the clinical significance of ELA in patients on PD and to evaluate the therapeutic effect of ELA on EMT of HPMCs. Compared with those in patients with stage 5 chronic kidney disease who are not on dialysis, serum ELA levels in patients on PD increased with the improvement of residual renal function at PD duration < 36 months and decreased to pre-dialysis levels at PD duration ≥ 36 months, suggesting that dialysis duration is the main risk factor affecting serum ELA levels in patients on PD. In addition, serum APLN levels decreased in the early stage of PD and recovered to the pre-dialysis level with the prolongation of dialysis time. Notably, serum APLN levels were positively correlated with dialysis duration in patients undergoing PD. To establish the EMT model, we stimulated HPMCs using transforming growth factor-beta 1 (TGF-β1) in cell experiments performed in vitro. ELA-32 treatment reversed the TGF-β1-induced reduction in the expression of the epithelial cell marker and suppressed the expression of mesenchymal cell markers by inhibiting the phosphorylation of SMAD2/3, ERK1/2, and AKT. Therefore, our findings imply that ELA-32 can interfere with the EMT of HPMCs by inhibiting the activation of the TGF-β/SMAD2/3, ERK1/2, and AKT pathways, providing novel insights on the potential therapeutic use of ELA for treating PD-related PF.